2011
DOI: 10.1152/advan.00011.2010
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary participation in an active learning exercise leads to a better understanding of physiology

Abstract: Students learn best when they are focused and thinking about the subject at hand. To teach physiology, we must offer opportunities for students to actively participate in class. This approach aids in focusing their attention on the topic and thus generating genuine interest in the mechanisms involved. This study was conducted to determine if offering voluntary active learning exercises would improve student understanding and application of the material covered. To compare performance, an anonymous cardiorespir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 25 publications
0
60
0
3
Order By: Relevance
“…"(Faculty) are stuck in their old ways and do not care enough to create engaging lectures." • Laziness or complacency (7). "Lazy, too much additional effort, easier to just show up and lecture."…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…"(Faculty) are stuck in their old ways and do not care enough to create engaging lectures." • Laziness or complacency (7). "Lazy, too much additional effort, easier to just show up and lecture."…”
Section: Resultsmentioning
confidence: 99%
“…Rather than focusing on rote memorization of fact, active learning encourages students to accomplish higher-order objectives on Bloom's taxonomy, such as analysis, synthesis, and evaluation (6). Studies (7,18,34) have indicated that active processing of information can improve students' comprehension of physiology, problem-solving abilities, and critical thinking skills.…”
mentioning
confidence: 99%
“…Quantitative student feedback on tutorials[1][2][3][4][5][6] Values are means (SD); average scores represent the average scores of the five questions asked for each tutorial. Students were asked to rate their response to a series of questions about each tutorial immediately after participation.…”
mentioning
confidence: 99%
“…In many institutions the traditional lecture continues to be the most used method, despite evidence showing that students who are taught primarily by traditional lecture have higher failure rates in science, engineering, and mathematics (Freeman et al, 2014). When provided with the opportunity to engage in active learning exercises, students assume responsibility for the material to be learned and are more likely to be able to apply that knowledge (Carvalho & West, 2011).…”
Section: Introductionmentioning
confidence: 99%